P5.087 Evaluation of the Multiplex AmpliSens HCV/HBV/HIV-FRT Real-Time PCR For Simultaneous Qualitative Detection of Hepatitis C RNA, Hepatitis B DNA and HIV RNA. (13th July 2013) - Malm, K; Unemo, M; Hedberg, S Thulin; Kireev, D; Andersson, S
Abstract : Background: Human donors of tissues and organs are obliged to undergo analysis for several blood transmitted infections. Serological assays are used, but for ideal sensitivity particularly for early infections these assays are beneficially supplemented with a nucleic acid amplification test (NAAT). For this as well as other diagnostic purposes, we have evaluated the multiplex AmpliSens HCV/HBV/HIV-FRT real-time PCR for simultaneous qualitative detection of HCV RNA, HBV DNA and HIV RNA in clinical plasma samples. Methods: Clinical plasma samples with known concentrations (according to viral load assays from Roche Diagnostics) of HCV (n = 34; range: 25 – 4.9×10 6 IU/mL), HBV (n = 30; 20 – 7.6×10 4 IU/mL) and HIV (n = 32; 34 – 4.7×10 5 c/mL); and samples from virus-negative blood donors (n = 100) were tested. Nucleic acid was isolated from 1 mL plasma on the MagNA Pure Compact using its Total Nucleic Acid Isolation kit I-Large Volume (Roche Diagnostics). The multiplex AmpliSens HCV/HBV/HIV-FRT real-time PCR (Central Research Institute of Epidemiology, Moscow, Russia) was run on a Rotor-Gene Q PCR instrument (Qiagen). Results: To date, 96 samples with various viral loads of HCV (n = 34), HBV (n = 30) and HIV (n = 32), have been analysed. Only three samples with very low concentrations of HCV (< 25–59 IU/mL) were false negative, and no false positive samples have been found. Complete data of the study will be presented at the meeting. Conclusion: The multiplex AmpliSens HCV/HBV/HIV-FRT real-time PCR proved to be highly sensitive and specific. Accordingly, this rapid, technically simple and low cost assay might be effectively used for screening of human donors as well as for other diagnostic purposes